The Effectiveness of Evidence Based Practice Educational Program in Undergraduate Nursing Students' EBP Knowledge and skills: A Cluster Randomized Control Trial - Cardoso, D.; Couto, F.; Cardoso, A.F.; Bobrowicz-Campos, E.; Teixeira-Santos, L.; Rodrigues, R.; Coutinho, V. (International Journal of Environmental Research and Public Health, 2021)
Evidence-based practice (EBP) prevents unsafe/inefficient practices and improves healthcare quality, but its implementation is challenging due to research and practice gaps. A focused educational program can assist future nurses to minimize these gaps. This study aims to assess the effectiveness of an EBP educational program on undergraduate nursing students' EBP knowledge and skills. A cluster randomized controlled trial was undertaken. Six optional courses in the Bachelor of Nursing final year were randomly assigned to the experimental (EBP educational program) or control group. Nursing students' EBP knowledge and skills were measured at baseline and post-intervention. A qualitative analysis of 18 students' final written work was also performed. Results show a statistically significant interaction between the intervention and time on EBP knowledge and skills (p = 0.002). From pre- to post-intervention, students' knowledge and skills on EBP improved in both groups (intervention group: p < 0.001; control group: p < 0.001). At the post-intervention, there was a statistically significant difference in EBP knowledge and skills between intervention and control groups (p = 0.011). Students in the intervention group presented monographs with clearer review questions, inclusion/exclusion criteria, and methodology compared to students in the control group. The EBP educational program showed a potential to promote the EBP knowledge and skills of future nurses.